How deans can use an executive coach. Issue 8 (26th March 2019) - Kalt, Stefan
Abstract : Sitting down at his new desk, Larry reflected anxiously on the scope of his new role. He was now dean of the College of Liberal Arts and Sciences. In the past, he had sometimes joined fellow faculty members and administrators in criticizing solutions to the college's problems offered by the previous dean. Now, he was the one mulling over solutions to these problems.